O jovem Nietzsche leitor de Wagner - Sochodolak, Hélio [UNESP] (Universidade Estadual Paulista Julio de Mesquita Filho, 2011)
Following clues from the young reader, Nietzsche, with regards to his intense and passionate relationship with music, we can historically approach his initial involvement in the Wagnerian cause during the late 1860s and early 1870s. The ideas and writings of Richard Wagner echoed Nietzschian concerns in his search for a style, for the sonorous quality in words, and for the enthusiasm of the reader. In his correspondence and in his writings, we see a young philologist (philosopher) excited, but sometimes suspicious: does Wagner represent an alternative to a new cultural model for the Germans in the second half of the 19th century? Could a musician teach a nation to establish new relationships through words? Could he teach a more artistic manner of reading?

Seguindo as pistas do jovem leitor Nietzsche em sua relação intensa e apaixonada com a música, abordamos historicamente seu envolvimento inicial com a causa wagneriana, no final da década de 1860 e inícios da década de 1870. Nas ideias e escritos de Richard Wagner os anseios nietzscheanos ecoaram em sua busca por um estilo, por uma sonoridade na palavra e por um arrebatamento do leitor. Em sua correspondência e em seus textos, percebemos um jovem filólogo(sofo) empolgado, mas, às vezes, desconfiado: Wagner representaria uma alternativa para um novo modelo cultural aos alemães na segunda metade do XIX? O músico poderia ensinar a nação a estabelecer novas relações com a palavra? Poderia ensinar a ler artisticamente?
The young Nietzsche, a reader of Wagner
Keywords: Young Nietzsche; Reading history; 19th century; Tragic quality; Jovem Nietzsche; História da leitura; Século XIX; Tragicidade